Strength efficiency factor of Strut-and-Tie Model elements in deep beams - Atika Ardianti Hadi. (2010)
Strut-and-Tie Model gains more recognition as a more accurate and versatile method for analyzing and designing deep beams. The current provision of using this method is explained in Appendix A of ACI Code 318-08. The adequacy of this provision was investigated upon 225 deep beam specimens that have been tested in laboratories. The analysis results revealed a possible area of improvement in determining strength efficiency factor for Strut-and-Tie Model elements. Some relevant aspects were taken into account, such as amount of web reinforcement, shear span-effective depth ratio, and concrete strength of concrete. The proposed modification involved the effect of shear span-effective depth (a/d) ratio, such that as a/d ratio decreases, the strength efficiency increases. This modification is illustrated to provide more accurate and consistent estimation of deep beam capacity. The modification is straightforward; it does not alter the simplicity of analyzing and designing with Strut-and-Tie Method. Other relevant aspects of deep beams and Strut-and-Tie Model were also studied; such as preferable analysis procedure, failure mode, and bearing failure efficiency factor. Thus, the completion of this project widens the view on design and behavior of deep beams.